OBJEKTIFIKASI HUKUM PERKAWINAN ISLAM DI INDONESIA PERSPEKTIF MAQASID SYAR’IYYAH UPAYA DARI INTEGRASI KEILMUAN KEISLAMAN - M Khoirul Hadi al Asyari (Program Studi Hukum Keluarga Islam, 2016)
This research is a study based on the Library Research and Field Research the pick-up scene on the excavation of Islamic Law through objectification theory in perspective of Maqasidh Sharia, in this studythere are three research questions: First, what and how is the concept of objectification of Islamic law?, Secondly, how is the implementation objectification of Islamic law in Indonesia? and the third is howObjectificationf Maqasid Shariah in Indonesia, with the approach of content analysis to examine the concept of objectification of Islamic law in Indonesia in Maqasid syar'iyyah perspective. The aims of thisstudy are first, to determine the concept of objectification of Islamic law. Secondly, it attempts to know the concept of objectification Law Islam in Indonesia, and third to know the objectification of Islamic Law in Indonesia from the perspective of Maqasid Shariah.